Distribution Investment Regulation : Principles and Practices in Power Sector of Armenia - World Bank (World Bank, Washington, DC, 2019)
The objective of this study is to identify the factors that need to be improved in the existing regulatory framework with respect to regulation of investments at the power distribution level. The study was initiated by the World Bank to inform the thinking of Public Services Regulatory Commission (PSRC) on further improvements that may be required in the process of preparation, review and approval of investments for power distribution company and some other incremental improvements in the regulatory framework for the power distribution. The primary aim of those improvements is to increase the efficiency of investments and clearly link those to the quality of electricity service for consumers. This link is currently not well-established, and the investment program submitted by the power distribution company does not clearly justify the relevant investments by the quantitative targets of electricity supply improvements. Additionally, there are some other inefficiencies in regulatory framework and end-user tariff structure. The study focuses exclusively on the investment planning, review, and approval issues related to power distribution company.